Author Correction: Mir142 loss unlocks IDH2R140-dependent leukemogenesis through antagonistic regulation of HOX genes - A. Marshall (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.